Babycart: a conceptual business model with benefits for parents and the B40 community - Sulaiman, Siti Nur Aishah; Hussain, Nurul Jannah; Ishak, Nur Ain; Ahmad Rasid, Nur Maisara; Ahmad Dahlan, Abdul Rahman (Kulliyyah of Information and Communication Technology, International Islamic University Malaysia, 2022)
The objective of this paper is to propose a conceptual BabyCart business model including a digital platform/apps that is aligned with United Nations Sustainable Development Goals (SDGs). The BabyCart business concept and platform offer potential benefits to its consumers given the new life advancement, new standards that people must adopt during this pandemic, and the rapid growth of technology. The intended users known as Customer Segments in this paper of this platform are low-income families or B40, single mothers, busy parents, and sellers. BabyCart offers a wide selection of baby products at a reasonable price as well as babysitting services. This paper identifies a few major issues and severe pain points for the customer segments and offers solutions for those issues. The key problems include poverty among Malaysians (SDG 1 - No Poverty), unemployment issues (SDG 8 - Decent Work and Economic Growth) and ensuring sustainable consumption (SDG 12 - Responsible Consumption and Production). This paper adapts the Design Thinking (DT) methodology in identifying key problems and developing possible viable solutions. This methodology includes conducting a literature review, benchmarking, and surveys/ interviews to understand and define customer segments’ problem space; as well as ideating, prototyping, and testing possible solution space. The business modeling tools namely the Environmental Map (EM), Business Model Canvas (BMC), Value Proposition Design Canvas (VPC), and Strategy Canvas (SC) were used both in the customers’ problem space as well as the solution space. An initial business model prototype was formulated – in the form of EM, BMC, VPC and low fidelity BabyCart prototype; tested and validated by various customer segments. Hence, the main contribution of this paper is to offer a validated or enhanced conceptual BabyCart business model as a conceptual solution in solving the unemployment issues for B40, increase sales for sellers and to give parents a digital platform where they can buy baby products.